Polyphenylglyoxamide-Based Amphiphilic Small Molecular Peptidomimetics as Antibacterial Agents with Anti-Biofilm Activity - Yu, Tsz Tin (Int J Mol Sci, 2021)
The rapid emergence of drug-resistant bacteria is a major global health concern. Antimicrobial peptides (AMPs) and peptidomimetics have arisen as a new class of antibacterial agents in recent years in an attempt to overcome antibiotic resistance. A library of phenylglyoxamide-based small molecular peptidomimetics was synthesised by incorporating an N-alkylsulfonyl hydrophobic group with varying alkyl chain lengths and a hydrophilic cationic group into a glyoxamide core appended to phenyl ring systems. The quaternary ammonium iodide salts 16d and 17c showed excellent minimum inhibitory concentration (MIC) of 4 and 8 μM (2.9 and 5.6 μg/mL) against Staphylococcus aureus, respectively, while the guanidinium hydrochloride salt 34a showed an MIC of 16 μM (8.5 μg/mL) against Escherichia coli. Additionally, the quaternary ammonium iodide salt 17c inhibited 70% S. aureus biofilm formation at 16 μM. It also disrupted 44% of pre-established S. aureus biofilms at 32 μM and 28% of pre-established E. coli biofilms 64 μM, respectively. A cytoplasmic membrane permeability study indicated that the synthesised peptidomimetics acted via disruption and depolarisation of membranes. Moreover, the quaternary ammonium iodide salts 16d and 17c were non-toxic against human cells at their therapeutic dosages against S. aureus.